HISTORICAL SHAPE AND THE PLANNING STRUCTURE OF HALYCH DURING THE 16–18TH CENTURIES - POLISHCHUK, Larysa (Halych. Scientific work collection, 2024)
Space-planning structure of Halych, formed during the XVI–XVIIIth, is a reflection of European urban planning theories and represents an overpass architectural and planning structure of ideal city with its irregular planning scheme, that combines elements of Middle Ages and Renaissance, and requires the development and implementation of specific programs concerning protection and preservation of the historic environment, which is threatened.